Recensión del libro “La conjetura de Anita” de Miguel Baraona - Chaves Murillo, Raúl (2025)
This review addresses critical and descriptive comments of the book La conjetura de Anita (Anita’s Conjecture), a literary work of tales from the Latin American context and its transculturations, by the chilean author Miguel Baraona Cockerell, published by the Editorial de la Universidad Nacional (EUNA) in 2024. The work is made up of eight stories and has been published with ISBN 978-9977-65-856-8.